The Corona debt conundrum in the Eurozone: Limits to stabilisation by monetary policy and the search for alternatives - Paweł Tokarski; Alexander Wiedman (Stiftung Wissenschaft und Politik (SWP), 2021)
One of the most serious economic and social consequences of the pandemic is the higher public debt of the Eurozone countries. The massive interventions of the Eurosystem have lowered borrowing costs to record lows. For some time to come, the sustainability of the public finances of the most indebted Eurozone countries will depend on expansionary monetary policy. However, this approach raises questions. It is uncertain how long monetary policy can support the debt market of the EU-19, whether there are effective alternatives, and what impacts the high debt levels and the interventions of the European Central Bank (ECB) will have on the foundations of the Eurozone.
Keywords: 320